The Land of the Great Image : Being Experiences of Friar Manrique in Arakan - Collis, Maurice (Brill | Manohar Publishers & Distributors, 2024)
This volume is based on the memoirs of the Augustinian friar Sebastien Manrique's expedition to South and Southeast Asia from ad 1590-1600. The biographical account begins with the intricate details about the Portuguese colony of Goa, which Manrique calls 'Golden Goa'. The author narrates Manrique's visit to a Jesuit-run hospital in Goa, his pilgrimage to Bom Jesus Basilica, and the embalmed mortal remains of St. Francis Xavier, the revered Roman Catholic saint of Goa. The memoir describes the Jesuit missionary's visit to the Mughal court under Akbar, Manrique's meeting with Roberto de Nobili and other Augustinian friars, and his visit to Bengal, around Hooghly, where an Augustinian monastery was located. The later part of this book contains his visit to the Burmese court and the vivid description of it, the assassination of the Arakanese monarch Thiri-Thu Dhamma, and the murder of Manrique himself. This book is highly important for studying the period of the Mughals and Arakanese Mrauk-U Kingdom from the late sixteenth to the early seventeenth century.